the The Effect of Job Responsibility, Emotional Intelligence, and Leadership on the Service Quality of Expert Staff for the People’s Representative Council of Indonesia - Taufiq, Moch. Aly; Madhakomala, R.; Supriyati, Yetti (International Journal of Scientific Research and Management (IJSRM), 2020)
This study was conducted to determine the effect of work responsibility, emotional intelligence, and leadership on the service quality of the expert staff of the People’s Representative Council of Indonesia (DPR RI). This study focused on the service quality of expert staff in the DPR RI using a quantitative approach with Structural Equation Modeling (SEM) method. 325 expert staffs of DPR RI from a total population of 1,725 were involved as the sample of this study. The empirical testing indicates that (1) there is a positive direct effect of job responsibility on service quality; (2) There is a positive direct effect of emotional intelligence on service quality; (3) There is a positive direct effect of leadership on service quality; (4) There is a positive direct effect of job responsibility on leadership; (5) There is a positive effect of emotional intelligence and leadership; (6) there is a significant positive indirect effect of job responsibility on service quality through leadership as the moderating variable; (7) the indirect effect of emotional (X2) on the service quality through leadership is positive and significant.